Psychological predictors of job performance and career success in professional sport - Stanimirovic, R.; Hanrahan, S. (Sport Science Review, 2010)
The measurement of psychological factors specific to sport has provided sport psychologists with valuable information for performance enhancement interventions. It is necessary, however, to consider that the predictive validity of the measures when related to job performance or career success in professional sport is limited (Humara, 2000). This literature review describes theoretical and empirical evidence related to (a) utility and validity of psychological measures that predict job performance, including general mental ability (GMA), personality, and emotional intelligence (EI); (b) descriptions of the psychological factors affecting successful and unsuccessful performances at major sporting events such as the Olympic Games; (c) examination of the psychological measures related to performance of successful athletes; and (d) an overview of EI as a construct relevant to job performance and career success of athletes. The aim of the literature review is to present evidence for a systematic method of assessment as recommended by Schmidt and Hunter (1998) that includes GMA and appropriate supplementary measures for sport. A method that encourages the existence and/or development of psychological competencies can enhance the professional experience for the athletes and potentially the return on investment for the professional sporting organization